Revisiting the Sectoral Linder Hypothesis: Aggregation Bias or Fixed Costs? - Hendrik W. Kruse (Luxembourg Income Study (LIS), 2016)
This paper reassesses and revisits the Sectoral Linder Hypothesis due to Hallak (2010), according to which similar tastes for quality lead to more intensive trade between similar countries. First, it will be shown that allowing for strictly non-homothetic preferences reduces confoundedness and improves results. Moreover, the country/firm level extensive margin is taken into account. This approach allows controlling for unobserved firm level heterogeneity and selection bias (Helpman et al. 2008). The advantage in terms of interpretation is that differences in coefficients at the two margins can be linked to fixed cost effects. The attempt is to show that the Linder effect is confounded with fixed (opportunity) costs of trade thereby leading to downward biased results. There is some evidence that this effect is exacerbated at the aggregate, intersectoral level. Fixed (opportunity) costs seem to be higher in sectors where similar countries trade a lot. The evidence reinforces the sectoral Linder hypothesis, and suggests that the patterns might prevail at the more aggregate levels. Other robustness checks suggest that results are not confined to products that are vertically differentiated.
Keywords: F14; D31; 330; International trade; income similarity; Linder hypothesis; strictly non-homothetic preferences; extensive and intensive margin of trade